2020
DOI: 10.5812/semj.96049
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Academic Procrastination Among Medical Students and Its Relationship with Their Academic Achievement

Abstract: Background: Procrastination is prevalent among university students and it affects different aspects of their personal and academic life. Objectives: This study aimed to determine the prevalence of academic procrastination among medical students and its relationship with their academic achievement. Methods: This is a cross-sectional correlational study of 317 medical students at Shiraz University of Medical Sciences. To collect the data, we used Solomon and Rothblum academic procrastination questionnaire (1984)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1
13

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 33 publications
3
42
1
13
Order By: Relevance
“…They also found a negative relationship in their study, showing that higher academic procrastination led to lower academic performance. Hayat et al (2020) also found a similar finding. They found out that a high level of procrastination was prevalent among students, leading to low academic achievement and chronic problems in learning.…”
Section: Findings and Discussionsupporting
confidence: 66%
“…They also found a negative relationship in their study, showing that higher academic procrastination led to lower academic performance. Hayat et al (2020) also found a similar finding. They found out that a high level of procrastination was prevalent among students, leading to low academic achievement and chronic problems in learning.…”
Section: Findings and Discussionsupporting
confidence: 66%
“…One of the most important goals of students at all levels is to achieve good grades and to have a high level of academic success that has significant positive outcomes for both students and the community. Thus, one of the major preoccupations of educational systems and educational psychologists is to identify the factors that influence students' academic performance (1)(2)(3). Students' academic performance is de pendent on a variety of factors not restricted to intelligence, teaching methods, gender, socioeconomic status, daily study hours, and study techniques (4- ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies are showing that there is a relationship between academic procrastination and low academic achievement (Beswick, et al., 1988;Carden, et al., 2004;Hayat, et al., 2020;Kim & Seo, 2016;Moores ,2013;Rothblum, et al., 2020;Solomon, & Murakami, 1986). On the other hand, there are various research results.…”
Section: Introductionmentioning
confidence: 99%